Potent antileukemic activity of curaxin CBL0137 against MLL‐rearranged leukemia. Issue 7 (8th August 2019) - Somers, Klaartje; Kosciolek, Angelika; Bongers, Angelika; El‐Ayoubi, Ali; Karsa, Mawar; Mayoh, Chelsea; Wadham, Carol; Middlemiss, Shiloh; Neznanov, Nickolay; Kees, Ursula R.; Lock, Richard B.; Gudkov, Andrei; et al.
Abstract : Around 10% of acute leukemias harbor a rearrangement of the MLL/KMT2A gene, and the presence of this translocation results in a highly aggressive, therapy‐resistant leukemia subtype with survival rates below 50%. There is a high unmet need to identify safer and more potent therapies for MLL‐rearranged (MLL‐r) leukemia that can be combined with established chemotherapeutics to decrease treatment‐related toxicities. The curaxin, CBL0137, has demonstrated nongenotoxic anticancer and chemopotentiating effects in a number of preclinical cancer models and is currently in adult Phase I clinical trials for solid tumors and hematological malignancies. The aim of our study was to investigate whether CBL0137 has potential as a therapeutic and chemopotentiating compound in MLL‐r leukemia through a comprehensive analysis of its efficacy in preclinical models of the disease. CBL0137 decreased the viability of a panel of MLL‐r leukemia cell lines ( n = 12) and xenograft cells derived from patients with MLL‐r acute lymphoblastic leukemia (ALL, n = 3) in vitro with submicromolar IC50s. The small molecule drug was well‐tolerated in vivo and significantly reduced leukemia burden in a subcutaneous MV4;11 MLL‐r acute myeloid leukemia model and in patient‐derived xenograft models of MLL‐r ALL ( n = 5). The in vivo efficacy of standard of care drugs used in remission induction for pediatric ALL was also potentiated by CBL0137. CBL0137 exerted its anticancer effect by trapping Facilitator of Chromatin Transcription (FACT) into chromatin, activating the p53 pathway and inducing an Interferon response. Our findings support further preclinical evaluation of CBL0137 as a new approach for the treatment of MLL‐r leukemia. Abstract : What's new? Rearrangement of the MLL/KMT2A gene results in a highly aggressive, therapy‐resistant leukemia subtype, with high incidence in infants and survival rates below 50%. In this preclinical study, the authors found that a new, small‐molecule curaxin drug called CBL0137 significantly reduced leukemia burden in xenograft models, and also enhanced the response to standard chemotherapy drugs. CBL0137 mediated this effect through activation of the p53 and IFN pathways. These findings support further preclinical evaluation of CBL0137 as a new approach for the treatment of MLL‐r leukemia.